LITERATURE REVIEW: REDUCING DYSMENORRHEA IN TEENAGER BY DRINKING TAMARIND TURMERIC WATER - Christina S, Lisberth; Ratnasari, Febi; Winarni, Lastri Mei (Universitas Airlangga, 2022)
Introduction: Menstruation is a sign of sexual development in adolescent girls. Abdominal cramps are one of the most common problems experienced by teenage girls during menstruation. Abdominal cramps occur due to the pulling of smooth muscles in the uterus which is usually followed by migraines, abdominal pain, weakness and excruciating pain. The average incidence of menstrual pain or dysmenorrhea in the world shows that more than 50% percent of women experience primary dysmenorrhea in Indonesia reaching 64. 25% with the category of 89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The purpose of this study is to examine scientific articles which discusses the reduction of menstrual pain in adolescents. Methods: The method used in this study is a literature review with data collection techniques using the Google Scholar, Pubmed, and e-resources database based on inclusion criteria, among others, the intervention in the form of giving sour turmeric stew, using the quasi experiment or pre experimental design or literature review method, using indonesian and english, published within 10 years (2011-2021). Respondents are teenagers who experience dysmenorrhea. Journals are accessible to the public. Results: The results showed that based on the study conducted, it can be seen that turmeric acid drink can reduce menstrual pain levels in adolescent girls because sour turmeric drinks contain curcumin and anthocyanins which are analgesics and antipyretics that function as pain relievers. Conclusions: So it is expected that young women consume traditional drinks, namely sour turmeric drinks when experiencing menstrual pain to reduce the pain they feel.